THE COMPARISON OF SEXUAL BEHAVIOR HIGH RISK SEXUAL BEHAVIOUR AND SELF-HARM BEHAVIOUR IN STIMULANTS/NARCOTIC SUBSTANCE ABUSE - Lale Mirsoleimani; Bagher Sanaee zaker; Shahram Vaziri (Drug Control Headquarters, Research and Education Office, 2009)
THE HYPOTHESIS, This survey compares the sexual behavior, the high risk sexual behavior and self-harm behavior of narcotic substance users (opium, crack, and heroin) with stimulants substance uses (ice, cocaine). METHOD, This survey is comparative-causative post test. The sample consisted of 265 substance abusers as intact subjects from different camps in Tehran who filled he sexual behavior questionnaire. The data were analyzed though ANOVA. RESULTS, the results showed that there is a meaningful difference between different groups of narcotic and stimulants substance users related to sexual behavior, high risk sexual behavior and self harm behavior. CONCLUSIONS, the level of sexual behavior in cocaine abuses was at the most and in crack abusers was at the least. Also, the level of high risk sexual behavior in ice and cocaine was more than opium, heroin and crack. The level of self harm behavior in crack abuses was more than ice and opium abuses.